The Influence of Brand Image, Service Quality and Digital Promotion on Decisions and Loyalty to Use CIMB Niaga Credit Cards - Andriana, Siska; Wahyuni, Sri (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research purpose is find out and analyze whether Brand Image, Service Quality and Digital Promotion influence Loyalty in using the CIMB Niaga Credit Card with customer decision asintervening variable This research method is quantitative research with a sample size of 106 respondents. Collection data technique is questionnaire. Data analysis technique is SEM through SmartPLS software. Brand Image not affecting Customer Loyalty, Brand Image affecting significantly Customer Decisions, Service Quality affecting significantly Customer Loyalty, Service Quality affecting significantly Customer Decisions, Digital Promotion affecting significantly Customer Decisions, Digital Promotion affecting significantly Customer Loyalty, Customer Decisions affecting significantly Customer Loyalty, Brand Image affecting significantly Customer Loyalty with Customer Decision as intervening variable, Service Quality affecting significantly Customer Loyalty with customer decision the intervening variable, Digital Promotion affecting significantly Customer Loyalty with customer decision as intervening variable